2017
DOI: 10.1021/acs.langmuir.7b02807
|View full text |Cite
|
Sign up to set email alerts
|

Critical Role of Surface Energy in Guiding Crystallization of Solution-Coated Conjugated Polymer Thin Films

Abstract: It is well-known that substrate surface properties have a profound impact on the morphology of thin films solution coated atop and the resulting solid-state properties. However, design rules for guiding the substrate selection have not yet been established. Such design rules are particularly important for solution-coated semiconducting polymers, as the substrate-directed thin film morphology can impact charge transport properties by orders of magnitude. We hypothesize that substrate surface energies dictate th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
105
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 69 publications
(111 citation statements)
references
References 80 publications
5
105
1
Order By: Relevance
“…Recent advances on the MGC crystallization mechanisms mainly depend on the surface energy (γ) analysis of the system. Zhang et al observed a better molecular packaging in the poly(diketopyrrolopyrrole‐thiophene‐thieno[3,2,b]thiophene‐thiophene) (DPP2T‐TTT) thin film when the system surface energy decreased . Similar results of surface energy regulation have been perceived by Vladimirov et al They observed n‐type crystals could start to grow at the solvent–air interface if the surface energy of solvents was higher than that of crystals .…”
Section: Introductionsupporting
confidence: 56%
“…Recent advances on the MGC crystallization mechanisms mainly depend on the surface energy (γ) analysis of the system. Zhang et al observed a better molecular packaging in the poly(diketopyrrolopyrrole‐thiophene‐thieno[3,2,b]thiophene‐thiophene) (DPP2T‐TTT) thin film when the system surface energy decreased . Similar results of surface energy regulation have been perceived by Vladimirov et al They observed n‐type crystals could start to grow at the solvent–air interface if the surface energy of solvents was higher than that of crystals .…”
Section: Introductionsupporting
confidence: 56%
“…We noticed that monolayer films could not be fabricated on surfaces with low surface energies (γ) such as OTS (γ = 20.5 × 10 −3 n m −1 ) because of dewetting of ink solution. Therefore, we chose substrates with higher surface energies as reference static substrates—plasma treated (γ = 67.2 × 10 −3 m m −1 )13 and phenyltrichlorosilane (PTS) (γ = 36.0 × 10 −3 n m −1 )13 functionalized SiO 2 (Figure S1, Supporting Information). We note that the surface energy of the IL used is comparable (γ = 36.2 × 10 −3 n m −1 )9 to that of PTS and thus rule out the effect of surface energy when comparing polymer films coated on IL versus PTS.…”
Section: Resultsmentioning
confidence: 99%
“…In fact, 2D monolayer could not be obtained at any printing speed attempted (0.1–100 mm s −1 at 0.5 mg mL −1 ) (Figure S6, Supporting Information). While the low surface energy of the PTS might have lowered the Gibbs' free energy for nucleation on PTS substrates compared to plasma treated SiO 2 ,13 the monolayer film was still riddled with voids, giving a film coverage of ≈86%. Quantitatively, we determined using an image analysis protocol we developed18 that the fractal dimension of the monolayer films on IL is 2, which significantly decreases to 1.33 ± 0.06 and 1.48 ± 0.05 for those on plasma SiO 2 and PTS, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…We propose a possible explanation to account for the trend of D P as a function of speed due to transition from free surface crystallization to substrate crystallization. At low speed, the high evaporation rate at the surface of the meniscus results a concentration gradient and a local supersaturation profile that promote free‐surface crystallization, whereas at intermediate speed, the thickness of meniscus decreases; therefore, heterogeneous nucleation is favored at the surface of the substrate . As the crystalizing environment differs, 2D diffusion coefficient on the substrate is much lower than on a free surface.…”
Section: Discussionmentioning
confidence: 99%
“…Morphology control is crucial to achieving high‐performance devices and to elucidating the complex structure–charge transport property relationship . Morphology is shown to be highly sensitive to processing conditions, such as printing/coating speed, solvent choices, substrate chemistry and topology, and so on. It has been widely shown that morphological parameters can modulate charge carrier mobility by orders of magnitude.…”
Section: Introductionmentioning
confidence: 99%